2005
DOI: 10.1111/j.1572-0241.2005.41957.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Histology Surrogate Markers (FibroTest-ActiTest) During Lamivudine Therapy in Patients with Chronic Hepatitis B Infection

Abstract: In patients with chronic hepatitis B, a 24-month course of lamivudine treatment leads to a significant decrease in necroinflammatory grades and fibrosis stages as assessed by noninvasive markers, with the occurrence of a three-phase kinetics. FT-AT should be useful in the noninvasive follow-up of lamivudine treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
94
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 39 publications
9
94
0
Order By: Relevance
“…In a larger study in patients with chronic hepatitis B, the FibroTest, which includes GGT as well as bilirubin, gamma globulin, haptoglobin, and α2 macroglobulin, has been reported to predict fibrosis stage ≥2 with an AUROC of 0.78, sparing biopsy for 46% of the patients, and with positive and negative predictive values of 92% in these 46% (38). Other studies performed by various groups have also indicated that FibroTest was a useful biomarker for predicting liver fibrosis in patients with hepatitis B infection (39,40).…”
Section: Discussionmentioning
confidence: 97%
“…In a larger study in patients with chronic hepatitis B, the FibroTest, which includes GGT as well as bilirubin, gamma globulin, haptoglobin, and α2 macroglobulin, has been reported to predict fibrosis stage ≥2 with an AUROC of 0.78, sparing biopsy for 46% of the patients, and with positive and negative predictive values of 92% in these 46% (38). Other studies performed by various groups have also indicated that FibroTest was a useful biomarker for predicting liver fibrosis in patients with hepatitis B infection (39,40).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, several studies suggest that certain marker combinations, such as Fibrotest, the enhanced liver fibrosis panel of ECM markers (ELF), or other selected ECM markers may have more value in predicting progression rather than fibrosis stage. [85][86][87][88][89][90] However, their validation as dynamic markers is difficult and will require more long-term studies. Such studies should also be complemented by determination of hepatic fibrogenesis by quantitative PCR for transcripts that are related to fibrogenesis or fibrolysis in matched liver biopsies.…”
Section: Noninvasive Means To Assess Liver Fibrosis and Fibrogenesismentioning
confidence: 99%
“…Considering recent research in which ECM markers or acute-phase proteins have widely been adopted as important components of fibrosis assessment in HBV related liver disease [23][24][25][26], it may seem surprising that both ECM markers and acute-phase proteins did not additionally contribute to the diagnosis of cirrhosis. Before such biomarkers are accepted, their superiority to routine laboratory data should be meticulously appraised.…”
Section: Discussionmentioning
confidence: 99%